2005
DOI: 10.1021/es048906i
|View full text |Cite
|
Sign up to set email alerts
|

Role for Fe(III) Minerals in Nitrate-Dependent Microbial U(IV) Oxidation

Abstract: Microbiological reduction of soluble U(VI) to insoluble U(IV) is a means of preventing the migration of that element in groundwater, but the presence of nitrate in U(IV)-containing sediments leads to U(IV) oxidation and remobilizaton. Nitrite or iron(III) oxyhydroxides may oxidize U(IV) under nitrate-reducing conditions, and we determined the rate and extent of U(IV) oxidation by these compounds. Fe(III) oxidized U(IV) at a greater rate than nitrite (130 and 10 microM U(IV)/day, respectively). In aquifer sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 74 publications
6
123
2
2
Order By: Relevance
“…As noted above, ferrihydrite may either compete as an electron acceptor in microbial respiration or may act as an oxidant of biogenic UO 2 . A series of recent reports indicate reoxidation of uraninite by Fe(III) at high concentrations of HCO 3 -resulting from bacterial respiration (Sani et al, 2005;Senko et al, 2005;. However, under the conditions of our study (HCO 3 -< 6 mM, 0.168 U(VI), and pH 7), even the oxidation of biogenic UO 2 to Ca 2 UO 2 (CO 3 ) 3 by ferrihydrite, the most viable reaction, would be thermodynamically favorable only at Fe(II) concentrations less than 0.025 mM Fe(II) during the initial stages of reduction and 0.050 mM at late stages.…”
Section: Impact Of Fe(iii) (Hydr)oxides On U(vi) Reductionmentioning
confidence: 99%
“…As noted above, ferrihydrite may either compete as an electron acceptor in microbial respiration or may act as an oxidant of biogenic UO 2 . A series of recent reports indicate reoxidation of uraninite by Fe(III) at high concentrations of HCO 3 -resulting from bacterial respiration (Sani et al, 2005;Senko et al, 2005;. However, under the conditions of our study (HCO 3 -< 6 mM, 0.168 U(VI), and pH 7), even the oxidation of biogenic UO 2 to Ca 2 UO 2 (CO 3 ) 3 by ferrihydrite, the most viable reaction, would be thermodynamically favorable only at Fe(II) concentrations less than 0.025 mM Fe(II) during the initial stages of reduction and 0.050 mM at late stages.…”
Section: Impact Of Fe(iii) (Hydr)oxides On U(vi) Reductionmentioning
confidence: 99%
“…In contrast to A. ferrooxidans, Fe(III) reducing Geobacter metallireducens, nitrate reducing Klebsiella sp., and sulfur oxidizing nitrate reducing Thiobacillus denitrificans enzymatically oxidize U(IV) at a near neutral pH under anaerobic conditions (Finneran et al, 2002b;Beller, 2005;Senko et al, 2005a). The enzymatic U(IV) oxidation is coupled to nitrate reduction and is not linked to energy conservation required for cell growth.…”
Section: Direct Enzymatic Control Of the Redox Transformations Of Umentioning
confidence: 99%
“…In its oxidized form, Tc is present as pertechnetate (Tc(VII)O 4 contaminant at nuclear sites (Fredrickson et al, 2004;Morris et al, 2000;Skomurski et al, 2010;Standring et al, 2002). By contrast, under reducing conditions, poorly soluble Tc(IV) species dominate, with hydrous TcO 2 -like precipitates forming at concentrations greater thañ 5610 À9 mol l À1 (Meyer et al, 1991), Tc(IV) sorption and retention to sediments observed at very low concentrations (<10 À12 mol l…”
Section: Introductionmentioning
confidence: 99%
“…Reoxidation of immobilized radionuclides in contaminated aquifers could occur via transport of oxygenated waters through the sediments, water table fluctuations, or disturbance of the geosphere by construction or erosion (Burke et al, 2006;Wu et al, 2007). Furthermore, reoxidation caused by nitrate, a common pollutant found at nuclear facilities, is also a potential route to radionuclide reoxidation via, for example, biologically mediated Fe(II)-oxidation coupled to NO 3 À reduction (Burke et al, 2006;Geissler et al, 2011;Morris et al, 2008;Senko et al, 2005;Wu et al, 2010;Law et al, 2010b;Law et al, 2011). Recent experimental work on sediments suggests that Tc associated with Fe(II)-bearing sediments is recalcitrant to reoxidation even though significant reoxidation of Fe(II) to Fe(III) occurs during both air and nitrate reoxidation (Burke et al, 2006;Fredrickson et al, 2009;Geissler et al, in press;Jaisi et al, 2009 .…”
mentioning
confidence: 99%